Analisa Komparatif Penerapan Strategi Aida pada Platform Instagram Merek Stella Mccartney dan Sejauh Mata Memandang - Prianka, Dian (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This research aims to analyze and compare the persuasive communication strategies used by Sejauh Mata Memandang and Stella McCartney on the Instagram platform. Through a qualitative approach, this research found that the two brands have different approaches in applying the AIDA model. Stella McCartney tends to use a more direct and transactional approach with an emphasis on calls to action (CTAs) to drive sales, while Sejauh Mata Memandang focuses more on building brand awareness and emotional connections with the audience through visually rich content with cultural elements and in-depth storytelling. This difference reflects the different target audiences and marketing objectives of the two brands. The implication of these findings is that fashion brands can adopt a variety of persuasive communication strategies on Instagram, depending on their marketing objectives and target audience. Brands with a global target audience and direct sales objectives can take a more transactional approach, while brands with local target audiences and long-term goals can focus on brand building and emotional connections. Further research is needed to explore the relative effectiveness of these different strategies in achieving brand marketing objectives.